2002
DOI: 10.1080/135562101200100147
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural aspects of areca nut use

Abstract: This paper aims to describe the sociocultural context of areca nut use through exploring people's norms and values and the meaning underlying a wide range of different practices. A historical review is followed by an examination of more recent evidence, including quantitative and qualitative research conducted in the United Kingdom. It is concluded that some reports involving the various uses of areca nut and the conclusions drawn are confusing and that future studies need to be more explicit. While a sound sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 15 publications
2
55
0
Order By: Relevance
“…Similar to research conducted in other ethnic enclaves, we found that the use was common even among individuals born outside of South Asia 34. Our results parallel prior studies outside of the USA finding incomplete or inaccurate knowledge of health risks and perception of benefits attributable to product use 17 27 35. For instance, South Asians in England, who have high rates of culturally specific tobacco use, generally have low levels of knowledge regarding the health risks imparted by these products 34.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to research conducted in other ethnic enclaves, we found that the use was common even among individuals born outside of South Asia 34. Our results parallel prior studies outside of the USA finding incomplete or inaccurate knowledge of health risks and perception of benefits attributable to product use 17 27 35. For instance, South Asians in England, who have high rates of culturally specific tobacco use, generally have low levels of knowledge regarding the health risks imparted by these products 34.…”
Section: Discussionsupporting
confidence: 86%
“…Few surveys assess variables such as perceived health benefits of tobacco use, a common belief among this community 17. For example, oral and digestive health benefits are ascribed to areca nut, an ingredient often added to smokeless tobacco preparations; these health beliefs originate from many South Asian religions 26 27…”
Section: Introductionmentioning
confidence: 99%
“…For an example, there was no difference found between the chewing habits of fi rst-and second-generation Bangladeshi migrations in the United Kingdom. [1,7] Strategies to prevent and control BN consumption are needed in order to prevent adverse health outcomes. An effective health promotion policy aimed at reducing the use of betel quid may reduce its use.…”
Section: Resultsmentioning
confidence: 99%
“…Almost 15% of the world's population (600 million people) currently has BN chewing habits. [1,2] Betel nut use is popular in India, Bangladesh, Sri Lanka, Myanmar, Maldives, Taiwan, and few islands in the South Pacifi c. It is also popular in many areas of Thailand, Malaysia, Indonesia, China, Philippines, Vietnam Cambodia, Laos, and among migrant populations from these countries residing around the world. Betel nut is an important agricultural product in these countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation